Evaluation: a key tool for improving drug prevention: papers from the Second European Conference on the Evaluation of Drug Prevention, 'Evaluation: A Key Tool for Improving Drug Prevention', held in Strasbourg, France, from 2 to 4 December 1999 - Neaman, Rachel (EMCDDA scientific monograph series, 2000)
This publication contains over a dozen expert contributions demonstrating how evaluation theory and knowledge can be implemented to improve drug prevention practice in the European Union. The monograph looks at both the practical and political aspects of evaluation and presents an array of tools, techniques and recommendations to improve drug prevention programmes and assess needs, processes and outcomes. Also demonstrated are ways to overcome obstacles that may weaken the evaluation process, such as poor communication between evaluators and policy-makers or conflicts between political agendas and poor evaluation results. This volume complements the EMCDDA’s second scientific monograph and forms part of a broad EMCDDA goal to promote an evaluation culture in Europe.